Petunjuk Kenabian dalam Berinteraksi dalam Kehidupan Sehari-hari - Ahmad Jihad Bawadi; Jefri Kurniawan; Rahma Jhony (IAIN Batusangkar, 2022)
After Allah swt created the prophet Adam AS, then he also created his life partner in the form of a woman who has given birth to this day, and will never break up until the angel Israfil blows his trumpet (doomsday) or the end of life. Replace with the real life, namely the afterlife. Before reaching eternal life, of course, humans must go through the life of the world and the twists and turns of life, hard, happy, happy, sad, and so on. In Islam, it has been regulated how to get along or socialize well with fellow living beings, both fellow Muslims and non-Muslims in order to create a harmonious life and there are no quarrels, let alone bloodshed. and this article will explain how good and right social procedures are, even though it is not a religion, considering that in this era there are so many who ignore it.